Design of defective ground plane modified microstrip patch antenna for ultra-wideband applications - Rasha H. Mahdi; Ahlam Alsudani; Mariam Qutaiba Abdalrazak; Hussein A. Abdulnabi (Universitas Ahmad Dahlan, 2024)
This study proposes a modified ultra-wideband (UWB) patch antenna with defective ground plane layout on FR-4 substrate material has dielectric constant ℇr equals to 4.3. An altered feed line has been employed to considerably enhance the antennas performance. Starting from 4 GHz to 13 GHz, upper, and lower frequency ranges can produce UWB antenna capabilities. The proposed antenna has a good bandwidth, making it practical to use in a variety of applications. Over the operational band, the reflection coefficient is decreased to less than -10 dB. The finite integral approach of fit is used to construct and analyze the antenna utilizing the computer simulation technology CST package simulator. In this study, an UWB antenna is demonstrated that may offer notches in the lower UWB band (3.1- 4 GHz). The performance of the antenna has been enhanced by using the flawed ground structure. The return losses and radiation characterstic confirm that the intended notched frequency has been suppressed. The proposed antenna was designed and simulated using computer simulation technology (CST 2020).